Association of visceral fat metabolism score with risk of rheumatoid arthritis in US adults - Li, Yonghui; Zhu, Yujuan; Tang, Xinwen; Guo, Zhiwen; Li, Jian; Lv, Shuchi; Liu, Meng; Yu, Yanjie; Lei, Changbin (Frontiers in Nutrition, 2025)
BackgroundThe Visceral Adiposity Index (METS-VF) has emerged as a novel obesity assessment metric. However, research exploring the relationship between METS-VF and rheumatoid arthritis (RA) remains limited. The objective of this investigation was to examine the correlation between the prevalence of RA and METS-VF.MethodsThe NHANES data collected between 2011 and 2018 were used in this investigation. To determine the association between METS-VF and the prevalence of RA, logistic regression analysis was used. Sensitivity and subgroup analysis were done to test how reliable the results were. Finally, the predictive power of BMI, waist circumference, and METS-VF for RA was compared using ROC curve analysis.ResultsThis research had 8,626 individuals in total. The findings showed that compared to those without RA, persons with the condition had noticeably greater METS-VF levels. METS-VF and the prevalence of RA were significantly positively correlated, according to a logistic regression analysis (OR = 1.50, 95% CI = 1.12–2.00). The results of the sensitivity and subgroup analyses agreed with the primary conclusions. ROC analysis indicated that METS-VF possessed a superior ability to predict RA compared to BMI and waist circumference.ConclusionThis study indicates that elevated METS-VF levels are positively correlated with an increased risk of RA in the US population. Monitoring this metric might aid in the early detection of high-risk patients.